1992
DOI: 10.1111/j.1365-2621.1992.tb06866.x
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit Lipoxygenase: Preparation and Characteristics

Abstract: Kiwifruit were analyzed for the presence of lipoxygenase (LOX) after mass-spectrophotometric analysis of kiwifruit pulp showed the presence of hexanal and hex-2-enal, considered to be break-down products of the reaction initiated by LOX. A spectrophotometric assay showed high levels of LOX when compared to other fruits and vegetables. Kiwifruit have at least one isoenzyme belonging to the class II group of LOX iso-enzymes, similar to -those identified in asparagus,-&-umber. tomato and aoole. The LOX reauired d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
4
14
0
1
Order By: Relevance
“…The alkali assay allowed measurement of protein to a level of 2 µg/mL. The alkali assay is now being used routinely in our laboratory for the measurement of soluble protein from plant tissues, enzyme preparations, wine and fruit juice (18,19,21,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…The alkali assay allowed measurement of protein to a level of 2 µg/mL. The alkali assay is now being used routinely in our laboratory for the measurement of soluble protein from plant tissues, enzyme preparations, wine and fruit juice (18,19,21,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Since LOX activity in sunflower is easily solubilized by mild detergents, such as 2 % Triton X-100, the association of LOX with the membrane does not seem to be very strong unlike other membrane proteins, such as oleosins, which can be extracted only by stringent procedures. Inclusion of Triton-X increases the recovery of LOX enzyme several-fold and has been reported to prevent enzyme inactivation in tomato membranes (Boyes et al 1992;Kato et al 1993;Smith et al 1997). The protonation and aggregation state of fatty acids are known to be determined by the pH of the medium (Cistola et al 1988).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, since it has been reported that the activity of some LOX isoenzymes is calcium dependant (Boyes et al, 1992;Robinson et al, 1995;Baysal & Demirdöven, 2007), the effect of calcium ion concentration on activity was also determined. Fig.…”
Section: Effects Of Temperature Ph and Calcium Ion Concentration On mentioning
confidence: 99%
“…LOX isoenzymes can be classified according to their optimum pH value of activity, their activation or inhibition by calcium ion and their capacity to co-oxidize carotenoids. LOX I shows its optimum activity at alkaline pH values (9.0-9.5) and has low carotenoid cooxidation activity; LOX II shows its optimum activity at acidic pH values (5.5-6.5), is activated by calcium and has high carotenoid co-oxidation activity; while LOX III shows activity at neutral pH, is inhibited by calcium and has a high capacity to co-oxidize carotenoids (Boyes, Perera, & Young, 1992;Robinson et al, 1995;Baysal & Demirdöven, 2007). Although the activity of LOX to cooxidize carotenoids is well known, the mechanism of the bleaching reaction is not totally understood.…”
Section: Introductionmentioning
confidence: 97%